PSORIASIS AND CARDIOVASCULAR DISEASE: IS IT CORRELATE? - Laksono, Sidhi; Candra, Wincent (Syifa'Medika, 2022)
Psoriasis is a common chronic inflammatory disease. This disease can cause a significant reduction in a person's quality of life. Systemic inflammation of psoriasis is thought to play a role in increasing the incidence of cardiovascular disease. Cardiovascular disease in psoriasis patients is a significant economic burden. Therefore, it is important for a doctor to understand and prevent the occurrence of cardiovascular disease in this population. This review aims to review the relationship between psoriasis and the incidence of cardiovascular disease, the underlying mechanisms, and the impact of the treatment of each disease on the other. There are overlapping risk factors for these two conditions. The underlying pathology of these two diseases is inflammation. The inflammation and treatment of one of these diseases might have an impact on the other. Psoriasis and cardiovascular disease are closely related to each other.